Operation of Circuit Breakers: Data and Analysis - Victory C. Madueme; M. J. Mbunwe; Theophilus C. Madueme; Mohammad Ayaz Ahmad; Cornelia V. Anghel Drugarin (Multidisciplinary Journal for Education, Social and Technological Sciences)
An attempt has been made for the analysis on Circuit breakers (CBs) this paper. First, the types and arcing phenomenon of Oil and SF6 Circuit breakers were briefly discussed. However, various CBs were analyzed in terms of certain outage frequencies and reliability indices to ascertain the most reliable CB. This was possible using data collected from the 33kV Transmission Company of Nigeria (TCN) New Haven, Enugu. After the analysis, Emene Industrial CB had the highest value of availability of 0.9999 and the lowest tripping report while Ezillo had the highest failure rate of 0.1032.